Chemical Constituents of Yarsagumba (Ophiocordyceps sinensis (Berk.) Sung et al.), a Valued Traditional Himalayan Medicine - Shrestha, Sabina; Shrestha, Bhushan; Park, Ji-Hae; Lee, Dae-Young; Cho, Jin-Gyeong; Baek, Nam-In (Nepal Journal of Science and Technology, 2013)
Ophiocordyceps sinensis (Berk.) Sung et al. is popularly known as Yarsagumba (winter worm summer grass) in Nepal. It is a well-known entomogenous fungus distributed in alpine nival zone of trans-Himalayas and Tibetan Plateau. Its occurrence in extreme biological niche and cohabitation with insect [Thitarodes (Hepialus)] larvae has led to unique assemblage of metabolites including proteins and nitrogenous compounds, polysaccharides, sterols, nucleosides, fatty acids and their derivatives, vitamins and inorganics. In traditional Chinese medicine, it is one of the most trusted main ingredients for several preparations of remedy from wide range of human health conditions. Several biological activities from O. sinensis have been reported that include anti-inflammatory, antioxidant, antitumor, anti-metastatic, immunomodulatory, antimicrobial, insecticidal, hypolipidaemic, hypoglycemic, anti-ageing, lipolytic, neuroprotective, renoprotective effects, etc. The chemical constituents and their pharmacological uses are reviewed here highlighting the potentiality of this highly esteemed traditional Himalayan medicine. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 43-58 DOI: http://dx.doi.org/10.3126/njst.v13i1.7398